Great House / Nicole Krauss. - Krauss, Nicole, 1974- (Penguin Books, 2010)
For twenty-five years, a reclusive American novelist has been writing at the desk she inherited from a young Chilean poet who disappeared at the hands of Pinochet's secret police, one day a girl claiming to be the poet's daughter arrives to take it away, sending the writer's life reeling. Across the ocean, in the leafy suburbs of London, a man caring for his dying wife discovers, among her papers, a lock of hair that unravels a terrible secret. In Jerusalem, an antiques dealer slowly reassembles his father's study, plundered by the Nazis in Budapest in 1944.